Assessing connectivity in coastal systems as a tool for fish management and conservation - Reis-Santos, P. (2013)
Tese de doutoramento (co-tutela), Biologia (Biologia Marinha e Aquacultura), The University of Adelaide, Universidade de Lisboa, 2013